Mass media, instrumental information, and electoral accountability / Christian Bruns - Christian Bruns; Oliver Himmler (Max Planck Institute for Research on Collective Goods, 2016)
Journalism is widely believed to be crucial for holding elected officials accountable. At the same time economic theory has a hard time providing an instrumental explanation for the existence of "accountability journalism". According to the common Downsian reasoning, rational voters should not be willing to pay for information out of purely instrumental motives because the individual probabilities of casting the decisive vote are typically very low. We show that this rationale does not apply when a group of voters shares a common goal such as accountability and information is delivered via mass media. In contrast to the pessimistic Downsian view, rational voters can have a considerable willingness to pay for the provision of instrumental information in these scenarios. Our model thus reconciles the rational voter approach with the common perception of journalism as a watchdog that holds elected officials accountable.
Keywords: D72; D83; H41; 330; accountability; elections; information; media